Hematospermia is rarely associated with urologic malignancy: Analysis of United States claims data. (5th May 2022) - Hakam, Nizar; Lui, Jason; Shaw, Nathan M.; Nabavizadeh, Behnam; Smith, James F.; Eisenberg, Michael L.; Breyer, Benjamin N.
Abstract: Background: Hematospermia is an alarming symptom and can cause significant patient distress, but work‐up is often negative. Objective: To characterize the clinical evaluation of hematospermia and its association with the diagnosis of urologic malignancy. Materials and methods: Using MarketScan insurance claims database, we identified adult males 18–64 years old diagnosed with hematospermia from 2010 to 2018. Benign hematospermia was defined as the absence of hematuria and elevated prostate‐specific antigen. Patients with urologic cancer prior to diagnosis of hematospermia were excluded. We identified those who were diagnosed with a urologic malignancy. Results: The annual average incidence rate of hematospermia was 56.6 per 100, 000 (95% confidence interval 55.4–57.8 per 100, 000) in 2010 and increased to 73.6 per 100, 000 (95% confidence interval 71.7–75.4 per 100, 000) in 2018. A total of 56, 157 patients presented with benign hematospermia. Most (57.5%) underwent at least one test, with the most common being urinalysis (51.7%), followed by prostate‐specific antigen testing (11.9%). All other tests were performed in less than 3% of patients. Forty‐seven patients were diagnosed with a urologic cancer, including 28 with prostate cancer (0.05%), nine with testicular cancer (0.016%), six with prostate carcinoma in situ (0.01%), and four with bladder cancer (0.007%). Stratified by age, there was only one cancer diagnosis (testicular) in 15, 106 patients under 40 years (0.01%) and 46 cancer diagnoses in 40, 611 patients 40 years old or above (0.11%). The median age of patients diagnosed with cancer was 56 years (interquartile range 52–61). Discussion and conclusion: A small minority of patients with benign hematospermia were later diagnosed with urologic cancer in a large nationally representative sample. After excluding hematuria with urinalysis, physicians should conservatively manage and reassure patients with hematospermia, especially those under 40 years of age.